Wednesday

March 4, 2015

March 4, 2015

Posted by **sw** on Monday, April 1, 2013 at 1:11pm.

g={(-3,6),(-2,4),(3,7),(6,-9)}

h(x)=2x-9

find the following

g^-1(6)=

h^-1(x)=

(h^-1 oh)(1)=

**Answer this Question**

**Related Questions**

Math- Please help - The one-to-one functions g and hare defined as follows. g...

algebra - one to one functions g and h are defined as g={(-4,5), (2,-5),(3,2, (4...

Algebra - Suppose that the functions q and r are defined as follows: q(x)=2x+1 r...

advanced functions/precalculus - 1. The function f(x) = (2x + 3)^7 is the ...

Math, Still Need Help! - Label each statement TRUE or FALSE. a. The sum of two ...

Math AP Calc - Label each statement TRUE or FALSE. a. The sum of two one-to-one ...

math - Suppose that the functions f and g are defined for all real numbers x as ...

Maths - Thanks steve for a brilliant answer! Got one last one which is ...

math - The application of one function followed by the application of a second ...

One to one functions - I still need help with finding the inverese of one to ...